2011
DOI: 10.1523/jneurosci.5989-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Plasticity of Vibrissae SII Representation Induced by Classical Conditioning in Mice

Abstract: The somatosensory cortex in mice contains primary (SI) and secondary (SII) areas, differing in somatotopic precision, topographic organization, and function. The role of SII in somatosensory processing is still poorly understood. SII is activated bilaterally during attentional tasks and is considered to play a role in tactile memory and sensorimotor integration. We measured the plasticity of SII activation after associative learning based on classical conditioning, in which unilateral stimulation of one row of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
2
19
1
Order By: Relevance
“…In agreement with this finding, it is anatomically well described that MI and S2 also receives thalamocortical projections from POm (Ohno et al 2012), that they are respectively interhemispherically connected Simons, 1987, Kinnischtzke et al 2014) and that they have corticothalamic projections to POm (Alloway et al 2008;Liao et al 2010). Moreover, POm is a strong driver of activity in S2 and M1 (Theyel et al, 2010;Castejon et al 2016;Casas-Torremocha et al 2019) and bilateral sensory responses in S2 have also been described (Debowska et al, 2011). However, it is important to note that the remaining ipsilateral activity that we found after S1 deactivation did not allow for the encoding and represention of ipsilateral tactile event duration or its spatiotemporal structure with high accuracy.…”
Section: Pom Mediates Bilateral Sensory Processing Pom Integration Ofsupporting
confidence: 58%
See 1 more Smart Citation
“…In agreement with this finding, it is anatomically well described that MI and S2 also receives thalamocortical projections from POm (Ohno et al 2012), that they are respectively interhemispherically connected Simons, 1987, Kinnischtzke et al 2014) and that they have corticothalamic projections to POm (Alloway et al 2008;Liao et al 2010). Moreover, POm is a strong driver of activity in S2 and M1 (Theyel et al, 2010;Castejon et al 2016;Casas-Torremocha et al 2019) and bilateral sensory responses in S2 have also been described (Debowska et al, 2011). However, it is important to note that the remaining ipsilateral activity that we found after S1 deactivation did not allow for the encoding and represention of ipsilateral tactile event duration or its spatiotemporal structure with high accuracy.…”
Section: Pom Mediates Bilateral Sensory Processing Pom Integration Ofsupporting
confidence: 58%
“…Our results prompt the question of by which route(s) is sensory information transferred from one POm to the other. Cortical responses to ipsilateral whisker stimulation have been described in the somatosensory cortex (Shuler et al 2001;Debowska et al, 2011). Therefore, ipsilateral activity seems to arrive at the contralateral POm by crossing the corpus callosum and descending from the cortex.…”
Section: Pom Nuclei Are Mutually Connected Through the Cortexmentioning
confidence: 99%
“…Recent electrophysiological data from the rat S2 have indeed reported that multi-whisker integration tends to be more supra-linear in S2 than in S1 23 . Moreover, a specific implication of S2 in bilateral integration is suggested from its connections with contralateral S1 and S2 9 and from experience dependent plasticity experiments 50 . It would be therefore of particular interest in the future to compare, by means of similar VSD imaging experiments, cortical dynamics evoked by both contra-and ipsi-lateral multiwhisker stimuli in S2 versus S1.…”
Section: Discussionmentioning
confidence: 96%
“…However, latency of responses in S2 to contralateral whisker stimulation is similar to that of S1, suggesting that POm is a major driver of sensory responses in S2 (Kwegyir‐Afful & Keller, ; Megevand et al ., ). S2 also possesses strong interhemispheric callosal connections and bilateral responses suggesting that it may be involved in integration of bilateral sensory information (Debowska et al ., ). During texture discrimination, S2 can similarly encode texture information as S1 from firing rate and spiking timing codes (Zuo et al ., ).…”
Section: Functional Properties Of M1 S1 and S2 During Behaviormentioning
confidence: 97%